Influence of Degree of Gelatinization on Expansion of Extruded, Starch‐Based Pellets during Microwave Vacuum Processing. Issue 3 (26th February 2014) - Kraus, Stefan; Enke, Nathanael; Gaukel, Volker; Schuchmann, Heike P.
Abstract The influence of the degree of gelatinization (DG) on microwave‐induced expansion of starch‐based, extruded pellets under vacuum was investigated. Expansion of extruded pellets with initial DG between 43.6 and 72.9% was investigated in a microwave vacuum drying system. With increasing DG, volume expansion showed a linear increase. The number of pores significantly increased at DG above 64.2%. A larger amount of water available might be the reason for the increased nucleation at large DG. The pore sizes decrease with increasing number of pores. If a larger number of bubbles is nucleated, a fewer amount of water can diffuse into every single bubble possibly resulting in lower water vapor pressure. No relationship between rheological and expansion properties of the matrix could be observed. We therefore assume that nucleation has the strongest effect on pore size distribution. Practical Applications In contrast to direct‐expanded extruded snacks, third‐generation snacks are generally produced by predrying nonexpanded, extruded pellets, followed by expansion to achieve a crispy and porous texture. By this procedure, extrusion can be performed at high moisture contents, moderate temperatures and moderate shearing conditions. This way, thermal‐ and mechanical‐sensitive ingredients can be preserved. A distinctive feature of the process investigated in this study is that the expansion is achieved by microwave vacuum processing, which allows an indirect expansion without the time‐ and energy‐consuming predrying process. This study shows that total volume and inner structure of the expanded pellets is influenced by the degree of gelatinization. With these information, producers can turn structure‐related properties such as appearance, crispiness and crunchiness to targeted values.